The transcription factor LEF1 interacts with NFIX and switches isoforms during adult hippocampal neural stem cell quiescence - García-Corzo, Laura; Calatayud-Baselga, Isabel; Casares-Crespo, Lucía; Mora-Martínez, Carlos; Julián Escribano-Saiz, Juan; Hortigüela, Rafael; Asenjo-Martínez, Andrea; Jordán-Pla, Antonio; Ercoli, Stefano; Flames, Nuria; López-Alonso, Victoria; Vilar, Marçal; et al. (Frontiers in Cell and Developmental Biology, 2022)
Stem cells in adult mammalian tissues are held in a reversible resting state, known as quiescence, for prolonged periods of time. Recent studies have greatly increased our understanding of the epigenetic and transcriptional landscapes that underlie stem cell quiescence. However, the transcription factor code that actively maintains the quiescence program remains poorly defined. Similarly, alternative splicing events affecting transcription factors in stem cell quiescence have been overlooked. Here we show that the transcription factor T-cell factor/lymphoid enhancer factor LEF1, a central player in canonical β-catenin-dependent Wnt signalling, undergoes alternative splicing and switches isoforms in quiescent neural stem cells. We found that active β-catenin and its partner LEF1 accumulated in quiescent hippocampal neural stem and progenitor cell (Q-NSPC) cultures. Accordingly, Q-NSPCs showed enhanced TCF/LEF1-driven transcription and a basal Wnt activity that conferred a functional advantage to the cultured cells in a Wnt-dependent assay. At a mechanistic level, we found a fine regulation of Lef1 gene expression. The coordinate up-regulation of Lef1 transcription and retention of alternative spliced exon 6 (E6) led to the accumulation of a full-length protein isoform (LEF1-FL) that displayed increased stability in the quiescent state. Prospectively isolated GLAST+ cells from the postnatal hippocampus also underwent E6 retention at the time quiescence is established in vivo. Interestingly, LEF1 motif was enriched in quiescence-associated enhancers of genes up-regulated in Q-NSPCs and quiescence-related NFIX transcription factor motifs flanked the LEF1 binding sites. We further show that LEF1 interacts with NFIX and identify putative LEF1/NFIX targets. Together, our results uncover an unexpected role for LEF1 in gene regulation in quiescent NSPCs, and highlight alternative splicing as a post-transcriptional regulatory mechanism in the transition from stem cell activation to quiescence.